Arogyavardhini Vati - A Boon for Liver Disorders from Ayurveda (Fatty Liver) - Dasi Padmaja; T Maheshwar; D Anuradha; Ch VS Koteswara Rao (AYUSHDHARA, 2021)
(NAFLD) or the Non-alcoholic Fatty Liver Disease is a global problem affecting a wide range of population associated with co-morbidities. Management of NAFLD is aimed both at managing the liver disease and also its co-morbidities. This is followed with an umbrella of therapeutic modules including lifestyle modifications, diet and the medications. Though both the modern medicine and Ayurvedic medicine follow the comprehensive approach in managing the disease, physicians will be very cautious with medications prescribed as those are associated with adverse effects. In this particular situation, Ayurvedic medicine such as Arogyavardhini vati plays a vital role in relieving the liver disorder, maintaining its health and also the health of digestive system thereby improving the overall health and the quality of life of the patient that is greatly disturbed with the liver disorders. Arogyavardhini vati that is considered one of the best for the liver disorders is critically reviewed in this study.